2020
DOI: 10.18502/ijph.v49i7.3574
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Mortality in COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: Background: The current study aimed to identify effective factors on the death among COVID-19 patients. Methods: All articles published in the period Jan 1, 2020, to Mar 23, 2020, written in English and reporting factors associated with COVID-19 mortality were reviewed. The random-effects model with 95% CI was used to calculate the pooled Odds Ratio (OR) and Hazard Ratio (HR). Data were analyzed using Stata ver.11.0. Results: The older age OR: 1.21(1.10-1.33) and male gender OR: 1.41(1.04-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 44 publications
8
71
1
8
Order By: Relevance
“…Several studies have indicated that comorbidities are one the strongest predictors of death or sever COVID-19 [22][23][24]. Another study from Iran showed that having comorbidities had a signi cant effect on mortality [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that comorbidities are one the strongest predictors of death or sever COVID-19 [22][23][24]. Another study from Iran showed that having comorbidities had a signi cant effect on mortality [20].…”
Section: Discussionmentioning
confidence: 99%
“…Essas duas comorbidades tĂȘm sido descritas como prevalentes em casos de SRAG por COVID-19, impactando de forma significativa no risco de morte de pacientes (Zhou et al, 2020;Sepandi et al, 2020). Os efeitos das comorbidades sobre o prognĂłstico da COVID-19 bem como de outras doenças respiratĂłrias infecciosas sĂŁo semelhantes (Sepandi et al, 2020).…”
Section: Resultsunclassified
“…Essas duas comorbidades tĂȘm sido descritas como prevalentes em casos de SRAG por COVID-19, impactando de forma significativa no risco de morte de pacientes (Zhou et al, 2020;Sepandi et al, 2020). Os efeitos das comorbidades sobre o prognĂłstico da COVID-19 bem como de outras doenças respiratĂłrias infecciosas sĂŁo semelhantes (Sepandi et al, 2020). Doença cardiovascular tem sido associada com eventos cardĂ­acos agudos e mal prognĂłsticos em infecçÔes por influenza e outras infecçÔes respiratĂłrias virais (Corrales-Medina et al, 2013;Udell et al, 2013).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Several studies on determinants of COVID-19 outcomes were identified in the literature; however, most of them were primary studies investigating risk factors for COVID-19 mortality (9, 10, 11). The few secondary studies/systematic reviews found in the literature encompassed only papers from high-income countries (12, 13). Also, there is inadequate coverage on other COVID-19 outcomes, specifically, length of hospital stay (LOS).…”
Section: Introductionmentioning
confidence: 99%